Researcher and community partner perspectives on community-engaged research during the COVID-19 pandemic - Simone C. Frank; Mary E. Grewe; Milenka Jean-Baptiste; Alicia Bilheimer; Alexandra F. Lightfoot; Laura Villa-Torres (Journal of Clinical and Translational Science)
Abstract